Non-Beta-Lactamase-Producing Penicillin-Resistant Enterococcus faecium in a Clinical Setting. (1990) - Eymard, Daniel; Dascal, Andre; Hiscott, John; Gioseffini, Sonia; Stevenson, Janet; Portnoy, Joseph; Mendelson, Jack
Abstract : Six clinical isolates of Enterococcus faecium highly resistant to penicillin are reported. These strains did not produce beta-lactamase and no plasmid DNA could be detected. It is postulated that the mechanism of resistance is one or more chromosomally mediated alterations of penicillin-binding proteins.